Impacts of the EducaSim School Management Platform on Teacher Routines in João Pessoa, Paraíba, Brazil (Global Journal of Human-Social Science, 2025)
This article investigates the impacts of the EducaSim platform on teaching routines analyzing its influence on school management usability and technological acceptance The research employed a qualitative approach based on questionnaires applied to teachers from Polo 1 of the Jo o Pessoa Municipal Education Network Para ba Brazil The results showed that EducaSim promoted advances in the organization and centralization of school data optimizing administrative and pedagogical tasks However challenges such as technical failures insufficient support lack of continuous training and increased teacher workload were highlighted as limitations to the platform s effectiveness Despite these issues the tool is widely perceived as innovative and essential for modernizing school management The article concludes that overcoming these challenges requires investments in technological infrastructure agile technical support and continuous user training With such improvements EducaSim could establish itself as a reference model in educational management promoting greater efficiency digital equity and quality in Brazilian public education
Keywords: platform; educasim; school management; sociotechnical networks; usability; technology acceptance model